2020
DOI: 10.1111/ijfs.14704
|View full text |Cite
|
Sign up to set email alerts
|

Influences of chitosan on freeze–thaw stability of Arenga pinnata starch

Abstract: This study aims to investigate chitosan (CS) with five different molecular weight (Mw) on freeze–thaw stability of Arenga pinnata starch (APS) gel subjected to five freeze–thaw cycles (FTC). The syneresis of APS gels was reduced by adding CS and the APS gel with high Mw CS had lower syneresis duo to a higher water holding capacity (P < 0.05). The addition of CS significantly decreased the hardness and molecular ordered structure of APS gel. In addition, CS could improve the microstructural stability. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
(59 reference statements)
2
11
0
Order By: Relevance
“…[8] More importantly, as observed in Figure 2, after seven FTCs, the hardness, gumminess of RS/XG-SPHs was significantly (p < 0.05) lower than that of RS. In detail, after FTC 7, the hardness of RS, RS/XG-SPHs was 290.98, 153.29 g, respectively, was de-creased by 137.69 g. Similar results were reported by Mei et al, [26] who reported that the addition of chitosan decreased the hardness of Arenga pinnata starch gel due to chitosan retarded the retrogradation of starch gel during FTC 5. The gumminess of RS, RS/XG-SPHs was 113.08, 54.57, respectively, was decreased by 58.51.…”
Section: Textural Properties Analysissupporting
confidence: 86%
“…[8] More importantly, as observed in Figure 2, after seven FTCs, the hardness, gumminess of RS/XG-SPHs was significantly (p < 0.05) lower than that of RS. In detail, after FTC 7, the hardness of RS, RS/XG-SPHs was 290.98, 153.29 g, respectively, was de-creased by 137.69 g. Similar results were reported by Mei et al, [26] who reported that the addition of chitosan decreased the hardness of Arenga pinnata starch gel due to chitosan retarded the retrogradation of starch gel during FTC 5. The gumminess of RS, RS/XG-SPHs was 113.08, 54.57, respectively, was decreased by 58.51.…”
Section: Textural Properties Analysissupporting
confidence: 86%
“…A background spectrum was recorded against an empty cell. The ratios of absorbance height 1047 cm −1 /1022 cm −1 were calculated to represent short-range ordered structure of starch (Mei et al, 2020b).…”
Section: Ft-ir Analysismentioning
confidence: 99%
“…HMT can improve thermal stability of APS, inhibit retrogradation and improve texture of APS gel (Funami et al, 2005). According to the previous research results, APS has shortcomings such as low anti-digestibility and poor freeze-thaw stability, which limit the application of APS in food processing enterprise (Mei et al, 2020b;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations